PHARMACOGNOSTIC EVALUATION OF TURMERIC (CURCUMA LONGA) EXTRACTS IN DIABETIC WOUND HEALING - M. A. Khan; T. Shahzadi; S. A. Malik2^; M. Shahid; M. Ismail; M. Zubair1; S. Iqbal (Journal of Animal and Plant Sciences, 2019)
Diabetic wound management has always been a challenge for health care providers and biomedical researchers. The present study was designed to investigate the wound healing potential of South Asian spice turmeric, which is rich in polyphenols, and honey in Alloxan-induced diabetic mouse model. Wound healing was improved significantly in topically applied turmeric, honey and insulin (as positive control) when compared with diabetic non-treated control, however highest wound healing was observed in the case of turmeric. Similarly, diabetic mice on oral turmeric showed improved healing as compared to the diabetic controls. Moreover, diabetic mice on oral turmeric showed enhanced glucose tolerance test. On the basis of above results we surmise that turmeric improves the healing activity in diabetic wounds by enhancing the glucose sensitivity. Our data emphasize the idea of using turmeric as ethnomedicine for diabetic wound healing.
Keywords: Curcuma longa; Pharmacology; Diabetes mellitus; Mice; Glucose Tolerance Test